O impacto do diagnóstico de anomalia congênita : coping e indicadores emocionais maternos - Vicente, Schwanny Roberta Costa Rambalducci Mofati (2013)
Congenital anomaly is characterized by any changes during embryonic development. When the baby is born with some kind of anomaly, the impact of such event may influence various social and affective aspects of the family dynamics. Therefore, this study aimed to verify the coping adopted by mothers of babies diagnosed with congenital anomalies and their stress, anxiety and depression levels, considering the influence of variables like the impact of the diagnosis and maternal beliefs about the development of the child. By signing the consent form, 25 mothers (M = 25.04 years) of children diagnosed with congenital anomalies (e.g.: congenital malformations of the circulatory system, of the nervous system, and of the digestive system) participated in the study. Their children were hospitalized in three Neonatal Intensive Care Units (NICU) of Vitória, ES. In the research’s first stage, the following instruments were applied: Socio-Demographic Data Questionnaire; Baby’s Data Questionnaire; News’ Moment Protocol; Economic Classification Criterion Brazil; Lipp’s Adult Stress Symptoms Inventory (ISSL, in Portuguese); and Beck Anxiety and Depression Inventory (BAI and BDI). In the second stage a semi structured interview was conducted with the objective to identify the child's development expectations, as well as the coping strategies adopted because of the congenital anomaly diagnosis and because of the baby’s hospitalization in the NICU. Data related to the standardized tests were analyzed according to the established normative criteria. The remaining obtained data were subjected to a qualitative analysis based on the Motivational Theory of Coping. The sample consisted of mothers who had more than one child (M = 2.33), who completed high school (n = 9), and had stable relationship (n = 23). The majority of mothers belongs to the class C1 (n = 9), i.e., living on an average income of R$ 1459. In 56% of the cases, the diagnosis was provided by obstetricians and, in 36%, by the pediatrician. For 40% of the mothers, the provided information was correct, but insufficient. Part of the sample (64%) positively evaluated how the physician communicated the diagnosis, but 76% of the responses were associated with negative feelings at the time of the news. Mothers emphasized the need for further explanation, i.e., although the mothers positively assess the news’ communication, they felt that more consistent information were lacking about the baby’s health and diagnosis. Regarding the stress, the majority (n = 12) of mothers was in the resistance stage, 6 at the almost exhaustion stage, and 3 in the exhaustion stage. 8 mothers showed moderate level of anxiety, 6 showed a mild level, and 5 showed a severe anxiety level. In the assessment of depression, 7 mothers had mild level of depression, 7 had moderate and 3 a severe level. Regarding coping, positive adaptive strategies such as Self Reliance and Seeking Support were very used by mothers. Negative adaptive strategies like Delegation and Helplessness were also used by the participants, a fact that requires attention from the health care team, as this fact may reflect negatively in the long run in their psychological wellness. Thus, from these results, it is confirmed that the diagnosis of congenital anomaly is a potential stressor for mothers and that the emotional and information demands should be considered by the health team during the diagnosis communication process. There is a need for interventions directed to mothers during hospitalization in order to reduce the negative emotional impact and to contribute for a better family adaptation to the condition of the child. It is emphasized the importance of studies on coping to support these interventions.